2019
DOI: 10.1159/000497805
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATE-AD and Tele-STAR: Novel Methodologies for Assessment of Caregiver Burden in a Telehealth Caregiver Intervention – A Case Study

Abstract: Aims: We explored the relationship between objective and subjective measures of burden prior to and after a telehealth-based caregiver intervention. One caregiver participated in two studies, one to assess the feasibility of objective, home-based monitoring (EVALUATE-AD), the second to assess the feasibility of a caregiver education telehealth-based intervention, Tele-STAR. Methods: Subjective measures of burden and depression in Tele-STAR and objective measures related to daily activities of the caregiver in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…These are presented in Table 2 . Table 1 and Table 2 lists articles in reverse chronological order: 2019 (4) [ 3 , 19 , 20 , 21 ], 2018 (12) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 2017 (14) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], 2016 (11) [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], 2015 (7) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…These are presented in Table 2 . Table 1 and Table 2 lists articles in reverse chronological order: 2019 (4) [ 3 , 19 , 20 , 21 ], 2018 (12) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 2017 (14) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], 2016 (11) [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], 2015 (7) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…We used the ROB 2 tool to evaluate 14 of the 15 studies for bias; however, we did not use it for the Spring et al (2009) study, because they reported only qualitative data. Of the 14 studies, 9 (64.3%) were appraised as having a “high risk” of bias, with the most common source stemming from the randomization process domain (Figueiro et al, 2015; Gibson et al, 2017; Jain et al, 2014; Paller et al, 2015; Simpson & Carter, 2010; Thomas et al, 2019). We deemed the remaining three studies as high risk due to significant concerns with measurement of the sleep outcomes (Elliott et al, 2010; Hirano et al, 2011) and intervention fidelity (Sloane et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies (Elliott et al, 2010; Figueiro et al, 2015; Fowler et al, 2016; Gibson et al, 2017; Hirano et al, 2011; Jain et al, 2014; Korn et al, 2009; Paller et al, 2015; Sloane et al, 2015) used a pre/posttest design, whereas the other six studies (Rose et al, 2009; Rowe et al, 2010; Simpson & Carter, 2010; Spring et al, 2009; Thomas et al, 2019; Williams et al, 2019) used repeated measures. The studies’ data collection schedules ranged from several weeks (Figueiro et al, 2015; Gibson et al, 2017; Hirano et al, 2011; Jain et al, 2014; Korn et al, 2009; Paller et al, 2015; Rose et al, 2009; Simpson & Carter, 2010; Sloane et al, 2015) to several months (Elliott et al, 2010; Fowler et al, 2016; Rowe et al, 2010; Spring et al, 2009; Thomas et al, 2019; Williams et al, 2019) Table 2 provides a summary of the included studies’ methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…Daily activity, determined via the number of total steps, was collected using the Withings Activite actiwatch (Withings; Issy-les-Moulineaux, France). This actiwatch has been used within the ORCATECH home assessment platform and specifically for studies related to the national Collaborative Aging Research using Technology (CART) initiative [ 45 ] and the Ecologically Valid Ambient Longitudinal and Unbiased Assessment of Treatment Efficacy in Alzheimer’s Disease (EVALUATE-AD) study [ 46 ]. The Withings Activite has previously been validated against the Actigraph wGT3X-BT (Pensacola, FL, USA) and StepsCount PiezoRxD (Deep River, ON, Canada) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%